2011
DOI: 10.1089/thy.2010.0232
|View full text |Cite
|
Sign up to set email alerts
|

Two Weeks of a Low-Iodine Diet Are Equivalent to 3 Weeks for Lowering Urinary Iodine and Increasing Thyroid Radioactive Iodine Uptake

Abstract: Two weeks of an LID are probably sufficient to augment thyroid uptake of ¹³¹I, with little or no benefit from longer periods of an LID. Questionnaires regarding exposure to iodine similar to those employed here should identify individuals in whom the LID has not been as effective in increasing the thyroid uptake of ¹³¹I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
2
15
0
1
Order By: Relevance
“…We hypothesize that one of the reasons for these equivalent data between 15-and 30-day RID is the lack of compliance of patients who went on an RID for 30 days, which made the UI results in this group similar to those of the patients who went on the diet for 15 days. Our results confirm the findings of Morsch et al [34] , who compared RID for 2 and 3 weeks and observed a significant UI decrease in both groups, with no difference between them.…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesize that one of the reasons for these equivalent data between 15-and 30-day RID is the lack of compliance of patients who went on an RID for 30 days, which made the UI results in this group similar to those of the patients who went on the diet for 15 days. Our results confirm the findings of Morsch et al [34] , who compared RID for 2 and 3 weeks and observed a significant UI decrease in both groups, with no difference between them.…”
Section: Discussionsupporting
confidence: 92%
“…However, no studies have convincingly demonstrated whether an adequate or slightly elevated iodine nutritional status has a negative impact on the treatment of hyperthyroidism. A single recent study compared the impact of an iodinerestrictive diet for 2 or 3 weeks on patients referred for investigation based on suppressed TSH levels associated with thyroid nodules and goiters (17). In this study, 2 and 3 weeks of a LID similarly decreased urinary iodine levels by 60%, which was accompanied by an approximately 40% increase in 131 I uptake by the thyroid.…”
Section: Discussionmentioning
confidence: 76%
“…To increase 131 I uptake, a stringent low-iodine diet (LID) is recommended and its efficacy is easily monitored by measuring urinary iodine levels (17,18). A LID reduces plasma iodine levels, leading to increased expression of sodium-iodide symporter (NIS), thereby increasing 131 I uptake (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Among studies that examined the LID, varying degrees of detail were provided about the implemented LID protocols. However, strict prohibition of all seafood and avoidance of all dairy products were commonalities observed among existing protocols . Many studies also restricted the consumption of canned foods as well as eating out at restaurants.…”
Section: Methodsmentioning
confidence: 99%
“…The current literature supports 1–2 weeks as the length for LID. There appear to be little to no benefit from greater than 2 weeks of a LID, as one study showed that the proportion of patients with UIC <100 mcg/l on a 3‐week LID (60·9%, n = 25) was not significantly different from that of patients on a 2‐week LID (63·2%, n = 21, P = 0·96) . Lastly, intense patient education and improved accessibility to medical staff may improve LID success rates and allow for a reduction in LID duration to 1 week, even in iodine‐replete areas.…”
Section: Methodsmentioning
confidence: 99%